Tarcrete management in Kuwait's Burgan oilfield - Kirkham, Elizabeth (2016)
Tarcrete is crude oil contamination that has formed across 175km2 of the Kuwait Burgan Oilfield as a result of the damage caused to production wells during the 1990 Gulf War. Remedial action on tarcrete affected areas is now being planned. The aim of this study is to evaluate the current tarcrete management objectives set as part of the UNCC Claim “Remediation of Areas Damaged by Tarcrete” by determining its effects on soil properties and vegetation establishment in the Kuwait Burgan Oilfield. A ground survey was undertaken to characterize its physical characteristics and develop a standard guideline for describing tarcrete. An intrusive investigation analysed tarcrete and the underlying soil. Soil temperature, moisture and electrical conductivity was monitored to evaluate the effects of tarcrete on these soil conditions. Vegetation cover was surveyed to evaluate potential effects on re-vegetation. Tarcrete occurred primarily as a “mat-like” continuous layer with an average thickness of 1.10+0.49cm, it was hardened and friable. A “gravel-like” fine to medium, very sparse, uneven, hardened, very friable to friable tarcrete type was also present. Chemical analysis detected TPH fraction C21-C35 (0.01% to 0.05%) and PHC fraction >C35-C90 (6% to 7%). SARA testing identified the main component to be polar heterocyclic molecules. This composition is representative of weathered crude oil. Metal concentrations were negligible and no PAH was detected. Contamination to the underlying soil was not detected nor were changes to the soil’s bulk chemical properties. Mean increase in soil temperatures of 4°C and 3°C was measured in areas of high and low tarcrete cover, respectively. Soil moisture showed a median increase of 62% and 58% at 100mm and 200mm depths in high tarcrete cover areas and 23% and 31% at 100mm and 200mm depths in low tarcrete cover areas. Moisture was retained in tarcrete areas. A mean increase in electrical conductivity occurred at high and low cover sites (68% and 19%) and were detected the longest at high tarcrete cover sites. Mean canopy cover at low tarcrete cover sites was 62% compared to 54% at high and no cover sites. This study illustrates tarcrete creates conditions that promote desert plant establishment depending on the ratio of tarmat cover to the percentage of fragmentation. Based on literature reviews and the Study Area conditions, is unlikely that planned remediation activities involving mechanical fragmentation will increase vegetation establishment. Instead, it will be potentially detrimental to the re-established vegetation so it is argued that the current tarcrete management objectives are unnecessary. The proposal to remove remedial intervention on the basis that tarcrete poses ‘no risk’ is recommended. No risk shall be verified via detailed quantitative human health and ecological risk assessments. Manual tarcrete fragmentation based on a fractioning index could enhance re-vegetation. Developing the index would require detailed quantitative measurements of the exposed soil vs covered soil, additional soil moisture and temperature monitoring and vegetation surveys and soil erosion studies.